2012
DOI: 10.1007/s13205-012-0102-4
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and selective ligninolysis of wheat straw and banana stem for an efficient bioethanol production using fungal and chemical pretreatment

Abstract: Lignocelluloses from agricultural, industrial, and forest residues constitute a majority of the total biomass present in the world. Environmental concerns of disposal, costly pretreatment options prior to disposal, and increased need to save valuable resources have led to the development of value-added alternate technologies such as bioethanol production from lignocellulosic wastes. In the present study, biologically pretreated (with the fungus, Pleurotus ostreatus HP-1) and chemically pretreated (with mild ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
2
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 32 publications
(38 reference statements)
4
25
2
7
Order By: Relevance
“…In this study xylanases activities were lower than those studies Silva et al (2005) and Thakur et al (2012) and superior to Chicatto et al (2014). This activity was not significant for L. edodes compared with exo and endocellulases.…”
Section: Treatments Dayscontrasting
confidence: 67%
“…In this study xylanases activities were lower than those studies Silva et al (2005) and Thakur et al (2012) and superior to Chicatto et al (2014). This activity was not significant for L. edodes compared with exo and endocellulases.…”
Section: Treatments Dayscontrasting
confidence: 67%
“…The cellulose was converted to reduction sugar at hydrolysis process followed by fermentation of the sugar to bioethanol. Alkali pretreatment can increase ethanol concentration was also reported by a study by [15]. …”
Section: Effect Of Different Pretreatments On Bioethanol Concentrationsupporting
confidence: 52%
“…Pleurotus ostreatus, a white rot fungus, is primarily a lignocellulosic biomass decomposer. Several reports show that P. ostreatus can effectively colonize many lignocellulosic substrates [5,[26][27][28], preferentially degrade lignin and leave the bulk of cellulose and/or hemicellulose behind [29,30]. Tests on the potential use of 3 agricultural wastes for cultivating Pleurotus species [5] indicated that the colonization rate of peanut shell substrates was significantly lower than cotton waste or wheat straw.…”
mentioning
confidence: 99%